Prosodic Entrainment in Conversations of Verbal Children and Teens on the Autism Spectrum - Lehnert-LeHouillier, Heike; Terrazas, Susana; Sandoval, Steven (Frontiers in Psychology, 2020)
Unusual speech prosody has long been recognized as a characteristic feature of the speech of individuals diagnosed with Autism Spectrum Disorders (ASD). However, research to determine the exact nature of this difference in speech prosody is still ongoing. Many individuals with verbal autism perform well on tasks testing speech prosody. Nonetheless, their expressive prosody is judged to be unusual by others. We propose that one aspect of this perceived difference in speech prosody in individuals with ASD may be due to a deficit in the ability to entrain – or become more similar – to their conversation partners in prosodic features over the course of a conversation. We investigated conversational speech with respect to prosodic entrainment behavior of children and teens with and without ASD as well as their conversation partners. Our results suggest (1) that youth diagnosed with ASD entrain less to their conversation partners compared to their neurotypical peers – in fact, children and teens diagnosed with ASD tend to dis-entrain from their conversation partners while their neurotypical peers tend to converge to their conversation partners’ prosodic features. (2) Although age interacts differently with prosodic entrainment in youth with and without ASD, this difference is predominantly attributable to the entrainment behavior of the conversation partners and does not constitute a true difference in the entrainment behavior of those with ASD. (3) Better language skill is negatively correlated with prosodic entrainment for both youth with and without ASD. The observed differences in prosodic entrainment in children and teens with ASD may not only contribute to the perceived unusual prosody in youth with ASD but is also likely to be indicative of their difficulties in social communication, which constitutes a core challenge for individuals with ASD.